Liquid‐Based Exfoliation of Black Phosphorus into Phosphorene and Its Application for Energy Storage Devices. Issue 5 (27th January 2021) - Rabiei Baboukani, Amin; Khakpour, Iman; Drozd, Vadym; Wang, Chunlei
Abstract : Black phosphorus (BP) as a rising star among 2D materials has attracted attention for a wide range of applications due to its fascinating properties. The key point for the real application of phosphorene depends on its exfoliation technique to produce high‐quality nanosheets. In recent years, tremendous efforts have been made in the preparation and energy storage application of phosphorene and phosphorene‐based hybrid electrodes. Herein, the state‐of‐the‐art liquid‐based exfoliation and characterization of phosphorene fabricated by sonication, anodic and cathodic electrochemical exfoliation, and bipolar electrochemical exfoliation in diverse solutions and conditions are discussed. In addition, the electrochemical properties and storage mechanism of phosphorene‐based electrodes for rechargeable batteries and supercapacitors are discussed. Finally, the challenges and opportunities of phosphorene nanosheets in terms of exfoliation and energy storage applications are addressed. Abstract : The emerged 2D black phosphorus has captured attention owing to its distinctive properties. Herein, the state‐of‐the‐art liquid‐based exfoliation of black phosphorus into phosphorene nanosheets via sonication, electrochemical cathodic/anodic exfoliation, and bipolar exfoliation are comprehensively summarized. Moreover, the electrochemical properties of phosphorene‐based electrodes for rechargeable batteries and supercapacitors and the challenges and opportunities for the future endeavor are highlighted.